Reasonable production allocation model of gas wells for deep tight gas reservoirs with the edge water - Huang, Weiting; Zhan, Zedong; Niu, Na; Xiao, Yihang; Shi, Yongheng (Frontiers in Earth Science, 2023)
Deep tight gas reservoir is one of the important unconventional gas reservoirs. Deep burial, tight reservoirs have many characteristics, including diverse accumulation patterns, multiple accumulation regulations, low natural energy generation, complex gas-water relationship and intricate seepage mechanism. These gas reservoirs feature requires new methods for a reasonable production allocation of horizontal well, optimization of such allocations from the perspective of stress sensitivity. While CO2 huff and puff based models, numerical simulation models and thermos-hydrodynamic models have been built to solve these issues, there is still lack of theoretical guidance for reasonable production allocation especially with the edge water problem. Here, we present a new one-dimensional mathematical and physical model to capture the stable movement of gas water interface in deep tight edge water gas reservoir. Our results show that there is a starting pressure in deep tight gas reservoirs. The starting pressure gradient increases with the growth of water saturation, which is far greater than the starting pressure gradient of medium shallow gas reservoirs under the same water saturation. In addition, by considering the stable movement of the gas water interface under the starting pressure, we found out that the gas well has a larger upper limit of production differential pressure, a smaller seepage velocity and a lower upper limit of production allocation. Finally, we make a comparison between our model results and production characteristics of real gas wells and find a consistency between model results with real data. Our model provides a theoretical framework for reasonable production allocation of gas wells in deep tight gas reservoirs with the edge water.